Model for Forming the Interregional Cluster of the Alternative Energy - Tyaglov, Sergey G.; Sheveleva, Anastasia V.; Shurukhina, Tatyana V.; Guseva, Tamara B. (International Journal of Energy Economics and Policy, 2019)
The relevance of the research is due to the necessity of improving Russia’s environmental and economic policy at the present stage and ensuring sustainable environmental and economic development of the Russian economy. One of the main strategic priorities of the latter is the development of alternative energy, which will contribute to higher energy and environmental efficiency as well as to easing the load on the environment. It will also involve optimization of the structure of the country’s balance of energy owing to reducing its dependence on the export of organic fuels and to ensuring innovation development of the energy industry for the long term. With regard to this, the paper is aimed at finding the most efficient way for solving the said problem; as one, it is shaping the interregional cluster of alternative energy that is suggested by the authors. The leading approach to studying this problem is the systemic approach enabling an integrated view of the diverse elements (alternative energy, cluster approach, interregional interaction) that used to be considered individually. In the paper, the necessity of developing alternative energy is justified as one of the focus areas for ensuring Russia’s sustainable environmental and economic development which requires the relevant material, labor and financial resources, technologies and equipment. In order to generate these, it is suggested to form the interregional cluster of alternative energy based on one of the four presented interregional interaction models, namely, the multilateral cross-sectoral model which is going to incorporate mutually associated sectors of the economy (producer sectors, supplier sectors, and consumer sectors) located in several regions and aimed at solving the shared problems. The materials of the paper are of practical value for the state and municipal authorities of Russia in terms of improving the policy implemented by them within sustainable development. Moreover, the results of the paper can be taken into account in forming an entire range of regulatory instruments and social and economic development programs for Russia in general and its regions in particular. Keywords: Alternative energy; cluster approach; interregional cluster; region; cluster policy JEL Classifications: C38, Q01, Q2, Q42 DOI: https://doi.org/10.32479/ijeep.7958